Argininosuccinate synthase 1, arginine deprivation therapy and cancer management - Sun, Naihui; Zhao, Xing (Frontiers in Pharmacology, 2022)
Metabolic reprogramming is an emerging hallmark of tumor cells. In order to survive in nutrient-deprived environment, tumor cells rewire their metabolic phenotype to provide sufficient energy and build biomass to sustain their transformed state and promote malignant behaviors. Amino acids are the main compositions of protein and provides key intermediate substrates for the activation of signaling pathways. Considering that cells can synthesize arginine via argininosuccinate synthase 1 (ASS1), arginine is regarded as a non-essential amino acid, making arginine depletion as a promising therapeutic strategy for ASS1-silencing tumors. In this review, we summarize the current knowledge of expression pattern of ASS1 and related signaling pathways in cancer and its potential role as a novel therapeutic target in cancer. Besides, we outline how ASS1 affects metabolic regulation and tumor progression and further discuss the role of ASS1 in arginine deprivation therapy. Finally, we review approaches to target ASS1 for cancer therapies.